Macedonia: coronary and structural heart interventions from 2010 to 2015 - Sasko Kedev; Biljana Zafirovska; Oliver Kalpak; Slobodan Antov; Jorgo Kostov; Igor Spiroski; Hristo Pejkov; Marjan Boshev; Ivan Vasllev; Aleksandar Jovkovski; Hajber Taravari; Danica Petkoska; et al. (European Association of Percutaneous Coronary Interventions, 2017)
The aim of this report is to describe invasive cardiology procedural practice in Macedonia during the period from 2010 to 2015. Details of all consecutive 39,899 patients who underwent cardiovascular, peripheral or structural heart procedures during the period from 2010 until 2015 were examined. Clinical and procedure characteristics, access site, procedural success and complications were analysed. The number of coronary angiographies increased from 5,540 in 2010 to 8,550 in 2015. Transfemoral access (TFA) was present in 4% of coronary angiographies in 2010 and had decreased to 1% in 2015. The number of primary percutaneous coronary interventions (PCI) for acute ST-segment elevation myocardial infarction increased from 763 to 1,175 and both chronic total occlusion and left main coronary artery interventions also increased over time. In 2015, the drug-eluting stent penetration rate was 65%. Structural heart interventions, including transcatheter aortic valve implantations (TAVI) were introduced in 2014 and 23 TAVI cases have since been performed. Transradial access was performed in 38,455 (96%) of all patients. Wrist access adoption in the majority of cardiovascular interventions is possible in all PCI centres in Europe if an appropriate national strategy is developed.